Dynamics of Economic Growth in West Sumatra: The Role of Digital Zakat and the Impact of Inflation through Financial Transformation - Aulia, Wahyu; Kamarni, Neng (ZISWAF, 2023)
Zakat isa  significant  source  of  funding  with  profound  implications  for economic growth, particularly in the West Sumatra region. However, there is an opportunityfor improvement sincethe actual collection in theregion falls below optimal standards. In recognizing theproblem, Zakat Forum (FOZ) developsthe idea of Digizakat, known asdigital zakat, to improve itscollection,and changes in the impact of inflation rates on thestability of the economy. Therefore, thisstudy aimed to examine the potential effects of inflation and digitally collected zakat on West Sumatra's economic growth   from short-and long-term perspectives. Secondary data from BAZNAS and BPS West  Sumatra are  used to  conduct a thorough analysis ofmonthly digital zakat collection records from 2016 to 2020.To evaluate the  impact of zakat digitization on economic   growth, Vector Autoregression(VAR) methodis  used. The results show that inflation  and  the digitization of zakat have a negligible short-term impact on regional economic growth.  Increased  literacy,  tighter  government  oversight, and maintenance of stable inflation rates are necessary to maximize the impact of zakat digitalizationto improve  economic  growth  and  public  welfare. This showsthe  necessity  for additional effortsand  the  development  of  intricate  models  to  comprehend  the variables  influencing  economic  growth, particularly the  adjustment  ofzakat digitalization to obtaina substantial impact